SILICOSIS, A MONUMENTAL OCCUPATIONAL HEALTH CRISIS IN RAJASTHAN-AN EPIDEMIOLOGICAL SURVEY - Mohammad, Shamim; Alharbi, Waheeb D.M.; Pasha, Tariq Sultan; Nour, Mohamed Osama Mustafa (International Journal of Research -GRANTHAALAYAH, 2017)
An epidemiological survey was carried out to assess the magnitude of silicosis in Karauli, a district located in the eastern part of Rajasthan. Silicosis, an occupational disease, which is caused by inhalation of the silica dust; marked by inflammation and scaring of the lungs resulting in nodular lesions in the upper lobes of the lungs. It is a fatal fibrotic pulmonary disease, which is irreversible in nature. Silicosis burden is substantial globally. In India, epidemiological surveys conducted time-to-time show that the problem is more severe in unorganized sector. Silicosis has emerged at epidemic level in Rajasthan due to exponential growth in the mining sector, inadequate Governmental policies, and poor implementation of the laws of the land. A study in 1992-94 carried out by the DMRC, Jodhpur reported that 9.9% sandstone workers have silicosis. A study conducted by the NIMH in Karauli (2013) revealed that 74% of them were suffering from the silicosis. However, all these surveys were conducted with the high-risk groups hence they are population measures. This survey intended to assess the magnitude of silicosis amongst the general population in the Karauli, one of the most backward districts of Rajasthan. A village (with approximately 1000 population) was considered as sample unit. Total 6 villages from the 4 regions of the district with a population of 6975 were covered in this cross sectional survey. All the adult population having respiratory symptoms and known history of mining were included in the study. Two questionnaires were used, one to gather occupational and medical history and the SGRPQ to assess the Health Related Quality of Life (HRQoL). The SGPRQ is a self-administered questionnaire, which produces activity, symptoms, and impact scores. Data were analyzed using SPSS software and Excel based analysis tool of SGPRQ. Results revealed that 2758 cases have been diagnosed with silicosis and 2267 cases with disease had received compensation from the Government till February 2017 in Karauli district. The Karauli block of the district had highest number of confirmed silicosis cases followed by Mandaryal, and Hindaun blocks of the district. The SC community is the worst affected (77%) followed by the ST (13%), OBCs (9%), and General community (<1%) ; 39% subjects had silicosis whereas 61% subjects had severe to mild respiratory difficulties with known history of sandstone mining activities and were categorized as suspected cases of silicosis. No women and no minors were found to have silicosis. The prevalence of the silicosis in all the 6 villages differed; overall prevalence was 12% (4% confirmed and 8% suspected cases). However, the prevalence of confirmed cases amongst the male (6+ years) was 10%. Variables exposure to silica dust is significantly correlated (p=0.01) with the smoking, the symptom, activity, impact, and total scores; implying that the higher the exposure to silica dust more the chances of developing the disease or severity of the symptoms and impact of the disease on quality of life.